CREATION AND USAGE OF CUSTOM GRADE SCALES IN BIOCHEMISTRY WEB BASED COURSE - Emilia Stoimenova; Simona Stoikova; Albena Jordanova (Science & Research)

(untitled)
Abstract: Blended learning was applied in biochemistry course in the master program at Faculty of Medicine, Sofia University. As a learning management system was used Moodle at the page www.elearn.uni-sofia.bg. Custom categories and grade items were created and used, to trace students' work and development through one school year education in biochemistry course. In this paper presents results from creation of different scales for assessment of the answers of the different tasks as clinical cases, protocols, term's definitions, results of a colloquium.